Impacts of intestinal microbiota metabolite trimethylamine N-oxide on cardiovascular disease: a bibliometric analysis - Leng, Xiaohui; Wei, Xiunan; Wang, Jun; Yao, Xiaodong; Zhang, Miaomiao; Sun, Dajuan; Liang, Junwei; Chi, Lili; Cheng, Yan (Frontiers in Microbiology, 2025)
BackgroundTrimethylamine N-oxide (TMAO), a metabolite dependent on intestinal microbiota, is closely related to the emergence, progression, and prognosis of cardiovascular disease (CVD), and has received increasing attention in recent years.ObjectiveThe current research hotspots and future development trends in TMAO and CVD field are found through bibliometrics analysis, which provides reference for further study.MethodsThe bibliometrics tools VOSviewer and CiteSpace were used to analyze the publications from the Web of Science Core Collection (WOSCC) database. The articles published from 2004 to 2024 about the relationship between TMAO and CVD were retrieved. Bibliometric analysis includes annual publications, countries/regions, institutions, authors and co-cited authors, journals and cited-journals, references and keywords.ResultsAfter searching and screening, 1,466 publications were included for subsequent bibliometric analysis. Since 2014, the number of publications exposing the relationship between TMAO and CVD has increased rapidly, as has the frequency of citations. China, USA and Italy are the countries that publish the most relevant research. Cleveland Clinic is the leading institution in this field. Stanley L Hazen, Zeneng Wang and W H Wilson Tang are the most prolific authors in this field, and the latter two have the closest academic cooperation. American Journal of Clinical Nutrition and Journal of the American Heart Association are influential journals that publish research in this field. “Gut Microbial Metabolite TMAO Enhances Platelet Hyperreactivity and Thrombosis Risk” is the most frequently cited article. Keyword analysis shows that gut microbiota, metabolism, phosphatidylcholine and atherosclerosis (AS) are the hotspots in this field.ConclusionThis study summarizes the research situation of TMAO and CVD in the past 20 years, focusing on the effect of TMAO on pathogenesis of AS, predictive value of TMAO on CVD risk, and dietary and drug intervention for TMAO. Probiotics and natural products may be the research focus of preventing and treating CVD by intervening TMAO in the future.